Pirólise catalítica do óleo de crambe para produção de biocombustíveis drop-in - Thales Silva Campos (2020)
The air pollution is one of the biggest problems currently in our society. Particularly the atmospheric pollution has been showing a risk to our planet once the amount of the emission of gases from the fossil fuels, such as CO2, NOx and SOx, have been growing exponentially. On the other hand, many alternative technologies to replace the mainly polluting agents, for example the fossil fuels, which emit gases that increase the greenhouse effect. Trying to minimize the large emission of these pollutants, alterative sources of energy have been studied aiming the total change or partially replacing the fossil fuels. The vegetable biomass it’s a promising alterative that can be transformed in energy through many different processes, such as thermal, biological or chemical. Otherwise, theses process must be economical attractive, to be insert on the market and compete with the currently consolidated energy matrix. This work, proposes as a alternative, the use of NbOPO4 as a catalyst to the production of biofuels, through pyrolysis of vegetable oils. The pyrolysis of the vegetable oils produces a liquid product denominated bio-oil, which is a mixture of diverse hydrocarbons and a certain amount of oxygenated compounds. Depending on the kinds and conditions of the experiments, this product can be utilized as biofuels or blends to them. The niobium phosphate was add, as a catalyst to the magnesium soap that was produced from the vegetal oil of crambe, and after it was pyrolyzed. The bio-oil, was characterized with spectrometric infrared (FTIR-ATR) and gas chromatography with mass detector (GC-MS). It was realized that the pyrolysis of the catalyzed soap leaded to a higher deoxygenation on the bio-oil produced and a slight increase of paraffinic compounds. Another important observation is that the higher percent of compounds produced on the bio-oil from the soap with no catalyst (50%) shows the range of carbons that can be compared with the green diesel fuel, and the second higher part (33%) with the compounds that represent the jet-fuel. The addition of NbOPO4 promoted a increase of the craking process, producing this way, a higher percentage of compounds with chains similarly to the jet-fuels (42%) and gasoline (32%). These results shows the potential that theses bio fuels have to be used as biofuels.